Affiliated Hospital of Shaanxi University of Chinese Medicine, Xianyang 712000, Shaanxi, China - Fan, Xinyue; Chen, Songtao; Liang, Shiqi; Xie, Wen; Shen, Lu (Journal of Contemporary Medical Practice, 2024)
With the progress of the times, the key pathogenesis of diabetes mellitus has gradually changed. Tong Xiaolin and other medical doctors, in response to the lack of Chinese medicine in the theoretical system of type 2 diabetes mellitus combined with obesity, after a long period of clinical practice, and combined with the theory of the “Nei Jing”, put forward the core mechanism of type 2 diabetes mellitus combined with obesity as “middle fullness and internal heat”, and created the “dispeling depression and clearing heat” as the basic treatment method [1]. The purpose of this paper is to review the clinical application research of the method of dispeling depression and clearing heat in the treatment of type 2 diabetes mellitus combined with obesity, which provides a reference basis for further in-depth research and rational use of medication.